Beyond The Kitchen: The Socio-Religious Authority of Women in Javanese Slametan - Himam, Mohammad Muafi; Dina, Dina (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
This study examines the pivotal role of women in the slametan tradition in Pungpungan Village, Bojonegoro, focusing on their authority in organizing, structuring, and adapting this Javanese ritual. While slametan is traditionally perceived as a male-led religious and communal event, this research reveals the significant influence women exert in determining key aspects of the ritual, particularly in food selection, scheduling, financial management, and intergenerational knowledge transmission. By exploring ethnographic accounts, this study highlights how women function as cultural custodians and ritual decision-makers, shaping both the practical and symbolic elements of slametan. The research also examines how food preparation extends beyond a domestic duty to a position of authority, with women dictating the culinary standards and ritual requirements. Additionally, the study illustrates the flexibility of slametan in adapting to contemporary sensibilities, showing how women negotiate tradition while maintaining its cultural essence. Through their expertise in managing rewang (communal labor), coordinating tahlilan, and determining religious offerings, women emerge as de facto leaders of the ritual. This study contributes to the broader discourse on gender and religious practices in Javanese Islam, challenging the perception of ritual authority as exclusively male and reaffirming the role of women as active agents in maintaining and evolving tradition.